A study on depression among paramedical students and the contributing factors in 2010-2011 - Nasiri Oskouei, Navideh; Kahkeshan, Parvin (Archives of Advances in Biosciences, 2013)
Depression in university students can be considered as an indicator of mental health. Therefore, it is highly important to be concerned about their mental health. The present research was conducted for the purpose of investigating the depression level in paramedical students and the contributing factors. This research is a cross-sectional study. The examined population included the students of a paramedical faculty and the sampling was done through census, selecting all the available students in the current semester. The questionnaire contained demographic questions and the Beck Depression Inventory (BDI), which were filled out by the students. Then, the depression level of students was determined with regard to the demographic questions and how each one associated with depression. For data analysis, an independent T-test, analysis of variance (ANOVA), and a correlation test were employed. In this research, the mean value and standard deviation score of students were 14.76 and 13.84 respectively. BS students scored 15.6, while MS and PhD students scored 7.7, which showed a significant difference between the two groups (p<0.001). The findings indicated that 20.6% of the students suffered from mild to moderate depression, while 9.9% of the students suffered from moderate to severe depression. The depression scores had no significant correlation with living place, marital status, gender, employment status, religious practice, previous semester GPA, and whether parents were alive. However, it had significant correlation with age(p=0.048), number of family members(p=0.004), satisfaction with study field(p=0.005), religious beliefs(p=0.028), extracurricular activities(p<0.001),, future career prospects(p=0.002), financial problems(p<0.001), satisfaction with relationships between family members(p<0.001), satisfaction with relationships between friends and classmates(p=0.003), satisfaction with relationships between university and faculty authorities(p=0.003),, as well as professors(p=0.022).Although some of the factors contributing to depression including age, number of family members and unpleasant life events cannot be prevented, most other factors or its results significantly leading to depression in students including extracurricular activities, satisfaction with relationships between family members, friends, classmates, university and faculty authorities, professors, and future career prospects can be controlled.